Occupation-Related Biological Health Hazards and Infection Control Practices among Indian Veterinarians - Rajendra Palkhade; SukhDev Mishra; Sukhadeo Barbuddhe (Veterinary Medicine International)
Veterinarians experience different types of health hazards from their occupation. Studies on the prevalence and occurrence of biological health hazards in veterinary medicine in India are scant and probably underreported. Thus, we sought to assess the biological health hazards and infection control practices (ICPs) among veterinarians from the states of Gujarat and Maharashtra, India. A cross-sectional survey was conducted among veterinarians (n = 562) from Gujarat and Maharashtra states in India to identify biological health hazards and ICPs for the prevention of occupational health hazards during 2016–2017 by personally contacting them. Responses regarding a biological hazard and ICPs were recorded. Descriptive analysis was attempted, and continuous variables are presented as the mean ± SD. Categorical variables are reported as counts and percentages (%). Most of the veterinarians (49.3%) worked in the field and were continuously exposed to different types of biological health hazards, especially zoonoses, ranging from mild and self-limiting to fatal diseases (e.g., brucellosis (subclinical and clinical form) and rabies (fatal)) without common prophylactic vaccinations, such as rabies and tetanus. While inquiring medical health status of the veterinarians, only 35.8% of the total respondents underwent a routine medical health checkup within the past year, and 56.9% did not receive a routine dose of an anthelmintic for deworming. Forty-nine percent of the respondents took all necessary precautions, including wearing an apron, facemask, and gloves. In contrast, 10.2% of the respondents wore only an apron, and 8.4% of respondents did not take any precautions while performing their day-to-day work. In total, 40.2% of the respondents followed the proper method of handwashing, that is, washing hands between patient examinations. In contrast, 27.9% of the respondents washed their hands once after completing the work. The majority of the respondents (87.7%) reported an urgent need for occupational hazards and safety (OHS) training in continued veterinary education (CVE) programs. The present study demonstrates that veterinarians in the states of Gujarat and Maharashtra in India pay less attention to their own health that may increase the risk of occupation-related biological health hazards. These results suggest that safety and ICPs are not prioritized, which are serious concerns. These findings may be useful for developing policies to prevent occupationally related biological health hazards among veterinarians in India.